2022
DOI: 10.3390/ijerph192013639
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Childhood Trauma and Family Functioning on Internet Addiction in Adolescents: A Chain-Mediated Model Analysis

Abstract: Objective: This study aimed to examine the prevalence of Internet addiction in adolescents, analyze the associations of childhood trauma, systematic family dynamics, and family functioning with Internet addiction, and investigate the mediating chain role of anxiety and depression in the relationship of childhood trauma and family functioning with adolescent Internet addiction. Methods: This was a cross-sectional study in which general sociodemographic data were obtained from 3357 adolescents in grades 6–12 who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Poor family intimacy or emotional expression can trigger depression in adolescents ( 40 ), and families that lack activities and effective communication are prone to developing more psychological problems ( 41 ). This result is also similar to those reported in a prior article from our group ( 42 ) that reported that poor family functioning was associated with poor FA and that adolescents from dysfunctional families were more likely to be prone to anxiety and depression. Li et al ( 17 ) found that the scores in all four dimensions of the SSFD were significantly improved following combined systemic family therapy in anxious and depressed adolescents with epilepsy.…”
Section: Discussionsupporting
confidence: 91%
“…Poor family intimacy or emotional expression can trigger depression in adolescents ( 40 ), and families that lack activities and effective communication are prone to developing more psychological problems ( 41 ). This result is also similar to those reported in a prior article from our group ( 42 ) that reported that poor family functioning was associated with poor FA and that adolescents from dysfunctional families were more likely to be prone to anxiety and depression. Li et al ( 17 ) found that the scores in all four dimensions of the SSFD were significantly improved following combined systemic family therapy in anxious and depressed adolescents with epilepsy.…”
Section: Discussionsupporting
confidence: 91%
“…More specifically, individuals who suffered psychological abuse were more likely to be addicted Internet compared to those suffered physical abuse. This difference in the strength of the association was indicated in two previous empirical studies (Hu et al, 2022;Schimmenti et al, 2017). Different forms of child abuse influence individuals differently due to the different effects on specific brain regions and circuits, psychological abuse is associated with persistent errors and difficulties (Montoya-Arenas et al, 2022).…”
Section: Explaining Heterogeneity With Moderatorsmentioning
confidence: 85%
“…More and more researches indicated that child abuse is a significant cause of Internet addiction (Hu et al, 2022; Lo et al, 2021). According to the life history theory, childhood experiences can affect individuals’ life strategies (Szepsenwol et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of intimate violence in the family also impacts adolescent Internet addiction. Due to a lack of emotional support from parents, adolescents are more likely to seek entertainment and friendship through the Internet, leading to excessive online addiction [25]. Problematic internet use refers to poor self-control and excessive internet use by young people [26].…”
Section: Introductionmentioning
confidence: 99%